2003 IEEE Bologna Power Tech Conference Proceedings,
DOI: 10.1109/ptc.2003.1304110
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo approach for assessment of investments deferral in radial distribution networks with distributed generation

Abstract: Distributed Generation @G) is located in distribution networks near to consumers or even in the consumers' side of the meter. Therefore, net demand to be supplied from transmission and distribution can decrease postponing the need to reinforce existing networks. This paper proposes a method to assess the impact of DG connection to radial distribution networks on investment deferral in the long-term. Due to the randomness of involved variables (load demand patterns, DG hourly energy production, DG availability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In [14] solar radiation in a time step is assumed to be dependent on the beam radiation, the diffuse radiation, the slope of the PV surface, the ground reflectance, the anisotropy and the cloudiness. In addition, the unavailability of the PV units is considered in [15].…”
Section: A Uncertainties From Pv and Loadmentioning
confidence: 99%
“…In [14] solar radiation in a time step is assumed to be dependent on the beam radiation, the diffuse radiation, the slope of the PV surface, the ground reflectance, the anisotropy and the cloudiness. In addition, the unavailability of the PV units is considered in [15].…”
Section: A Uncertainties From Pv and Loadmentioning
confidence: 99%
“…The penetration of distributed generation into a given distribution system could be measured through an individual penetration index [11] associated with the generator i:…”
Section: Distributed Generation Penetrationmentioning
confidence: 99%
“…In the last decade, it has been reported that the network upgrade deferral is an attractive option for DG planning to meet load growth [61][62][63]. The study in [61] showed that depending on technologies adopted, DG units have diverse impacts on the network deferral. For example, due to their intermittency, wind units have the ability to release the overloads of power networks less than CHP units.…”
Section: Network Upgrade Deferralmentioning
confidence: 99%